2022
DOI: 10.46660/ijeeg.vol12.iss4.2021.640
|View full text |Cite
|
Sign up to set email alerts
|

Impact Assessment of Urban Built-up Area on Groundwater Level of District Faisalabad, Pakistan

Abstract: This paper attempts to explore the impact of built-up areas on groundwater levels in district Faisalabad.To understand the rate of built-up area expansion and changes in the level of groundwater in the study area, groundwaterdata has been acquired from the Land Reclamation Department for all tehsils in district Faisalabad. This study wasconducted to assess spatial and temporal variation of groundwater level because of the built-up area change. Descriptivestatistics (Scatter Plot correlation technique) have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Other researchers in different study regions have found a strong relationship between groundwater depletion caused by human actions and land-use change [33,57,58]. For example, Zia et al [59] investigated the impact of a built-up area on groundwater and revealed that the built-up area in the district is increasing by 36 km 2 per year, and consequently, the water table is depleting up to 0.14 feet per year.…”
Section: Relationship Of Land-use and Climate Changes With Groundwatermentioning
confidence: 99%
“…Other researchers in different study regions have found a strong relationship between groundwater depletion caused by human actions and land-use change [33,57,58]. For example, Zia et al [59] investigated the impact of a built-up area on groundwater and revealed that the built-up area in the district is increasing by 36 km 2 per year, and consequently, the water table is depleting up to 0.14 feet per year.…”
Section: Relationship Of Land-use and Climate Changes With Groundwatermentioning
confidence: 99%